Systemic Modelling of Design Error Causation in Social Infrastructure Projects - Love, Peter; Lopez, Robert; Goh, Yang Miang; Davis, Peter (Elsevier, 2011)
Design errors contribute significantly to cost and schedule growth in social infrastructure projects and to engineering failures, which can result in accidents and loss of life. Despite considerable research that has addressed their error causation they still remain prevalent in projects. This paper develops a conceptual model of the underlying conditions that contribute to design errors in social infrastructure projects. A systemic model of design error causation is then propagated. The research suggests that a multitude of strategies should be adopted in congruence to prevent design errors from occurring and so ensure that safety and project performance are ameliorated.